Oxidation of 6-Phosphogluconolactonase Mediated by Peroxyl Radicals Affects Specific Amino Acids and Triggers Protein Aggregation: Consequences for the Pentose Phosphate Pathway - Arenas-Salinas, F (ELSEVIER SCIENCE INC, 2023)
Sin Resumen Disponible